The Impact of Islamic Corporate Governance, Corporate Social Responsibility, and Sustainability Reporting on Financial Performance: A Quantitative Analysis of Islamic Banks in Asia (2017–2023) - Ridwansyah, Ridwansyah; Mujahid, Ahmad (Institut Agama Islam Sunan Giri Ponorogo, 2025)
Where the intent of This inquiry is to analyze the repercussion of the independent elementon the dependent elementon Islamic banks in Asia Inquiry year 2017-2023.This inquiry is a quantitative inquiry. This inquiry utilizes secondary data sourced from the official websites of each company, including the Annual Report, Financial Report, and Sustainability Report. The target group in This inquiry are Islamic banks in Asia. The sample of This inquiry consisted of 10 Islamic banks in the period 2017 to 2023. Up to 70 samples. The sampling method in this inquiry employs purposive sampling. The data examination technique utilized is multiple linear regression examination, conducted using the SPSS 25 software. The Discoveries of this inquiry exhibited that Islamic Corporate Governance variables have both partial and simultaneous repercussions on Financial performance. However, Islamic Corporate Social Responsibility and Sustainability Reporting do not have a partial repercussion on Financial performance. Meanwhile, when considered together, all independent variables collectively sway the dependent variable. Financial performance strives to enhance the resilience and competitiveness of Financial Services Institutions and has the principle of risk management, capacity building in the implementation of sustainable finance so that it can grow and develop sustainably.